2023
DOI: 10.3389/fimmu.2023.1086342
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of prognostic value and immunological roles of RAB22A in hepatocellular carcinoma

Abstract: BackgroundThe protein-coding gene RAB22A, a member of the RAS oncogene family, is amplified or overexpressed in certain cancers. However, its action mechanism in hepatocellular carcinoma (HCC) remains unclear. Here, we aimed to examine the connection between RAB22A and survival prognosis in HCC and explore the biological significance of RAB22A.MethodsA database-based pan-cancer expression analysis of RAB22A was performed. Kaplan–Meier analysis and Cox regression were performed to evaluate the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In recent years, much progress has been made in understanding the pathogenic properties of Rab22a. For instance, many studies have confirmed that Rab22a is upregulated in and closely linked to the progression of various malignant tumors, especially in the HCC 5,136–138 . However, in the inverse of its pro‐oncogenic role, Rab22a‐induced extracellular vesicle (R‐EV) released from the exocytosis of Rab22a‐mediated noncanonical autophagosome fused with EE (Rafeesome) is a novel EV type that induces antitumor immunity 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, much progress has been made in understanding the pathogenic properties of Rab22a. For instance, many studies have confirmed that Rab22a is upregulated in and closely linked to the progression of various malignant tumors, especially in the HCC 5,136–138 . However, in the inverse of its pro‐oncogenic role, Rab22a‐induced extracellular vesicle (R‐EV) released from the exocytosis of Rab22a‐mediated noncanonical autophagosome fused with EE (Rafeesome) is a novel EV type that induces antitumor immunity 34 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, many studies have confirmed that Rab22a is upregulated in and closely linked to the progression of various malignant tumors, especially in the HCC. 5,[136][137][138] However, in the inverse of its pro-oncogenic role, Rab22a-induced extracellular vesicle (R-EV) released from the exocytosis of Rab22amediated noncanonical autophagosome fused with EE (Rafeesome) is a novel EV type that induces antitumor immunity. 34 We summarize recent research on the basic information of Rab22a and the BLOC-1-Rab22a-BLOC-2-KIF13A-AnxA2 complex-induced recycling tubule biogenesis as well as and the role Rab22a in cargo-specific recycling in this review.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we carried out the normality test for the numerical type of variables and used the expression median to categorize the groups. When the data meet the normal distribution, we will calculate the mean ± standard deviation (SD) with the Z-score transform of the corresponding variables; If it does not conform to the normal distribution, the median of the related variables (upper quartile and lower quartile) will be calculated [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…RAB22A is a member of RAS oncogene family, and its expression is increased in many cancers such as breast cancer [ 10 ], colorectal cancer [ 11 ], osteosarcoma [ 12 ] and liver cancer [ 13 ], and it is involved in the proliferation, migration and immune regulation of malignant tumors. As a small GTPase, RAB22A belongs to RAB5 subfamily, mainly located in early endosomes, Golgi bodies and late endosomes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…RAB22A controlled MHC-I intrinsic distribution, recycling and trafficking to dendritic cell (DC) phage, which played an extremely important role in the antigen cross-presentation reaction of DC [ 19 ]. In another study, RAB22A was significantly up-regulated in hepatocellular carcinoma, which was significantly related to the infiltration of various immune cells and the gene expression of immune checkpoints, and may lead to poor prognosis of hepatocellular carcinoma by regulating immune function [ 13 ]. However, RAB22A is rarely studied in hematological tumors, and there is no related research in MM at present.…”
Section: Introductionmentioning
confidence: 99%